B-Type Natriuretic Peptide and Ventricular Dysfunction in the Prediction of Cardiovascular Events and Death in Hypertension. (4th October 2017) - Gallagher, Joe; Watson, Chris; Zhou, Shuaiwei; Ryan, Fiona; Ledwidge, Mark; McDonald, Kenneth
Abstract: BACKGROUND: The prevalence and morbidity of hypertension continues to grow globally and improved methods of stratifying risk and identifying organ damage earlier are required. Methods such as echocardiography and population-based risk scores are suggested by guidelines as approaches to aid in risk stratification. However, biomarkers such as natriuretic peptides may help provide such an approach. METHODS: We analyzed data from the screening to prevent heart failure cohort including participants with hypertension with and without a history of a cardiovascular (CV) event at baseline. We investigated the ability of ventricular dysfunction on echocardiography at baseline and of B-type natriuretic peptide (BNP) levels in predicting future major adverse CV events (MACE) and death. We also investigated the use of Systematic COronary Risk Evaluation (SCORE) to predict these events in the uncomplicated cohort. RESULTS: In total, 572 patients (427 with uncomplicated hypertension) were included. Thirty-three patients had MACE or died during follow up. In a univariate analysis, BNP was predictive of MACE and death in all groups. Ventricular dysfunction was not predictive of MACE and death in any group. Both BNP and SCORE had predictive value in this category. However, the magnitude and strength of the continuous association between BNP and events is higher and BNP adds significantly to the predictive value of SCORE as determined by likelihood ratios. The net reclassification improvement for BNP compared to stage B heart failure was 0.20. CONCLUSION: This study demonstrates that in patients with hypertension, BNP is superior to ventricular dysfunction on echocardiography in the prediction of risk of MACE and death in a community-based cohort of patients with complicated and uncomplicated hypertension.